Structural and optical properties of electron-beam evaporated Al(2)O(3)-doped V(2)O(5) thin films for various applications - Ali, Hapipah Mohd; Hakeem, A.M.A. (2010)
The solid state reaction method was used to prepare tablets of (V(2)O(5))(100-x) (Al(2)O(3)) x with x =5.10 15.20 wt % thin film of Al(2)O(3) doped V(2)O(5) were deposited onto glass substrated using and electron beam evaporation technique. The influence of doping and annealine temperature on the structural and optical characteristics has been investigated in detail Optical properties of the films were studied extensively in the wavelength range 200-2500 nm from the measurements of the optical transmittance (T) and optical reflectance (R). It was observed that the optical properties such as transmittance, reflectance optical bandgap, and refractive index of (V(2)O)(100) (Al(2)O(3)) films were strongly affected by the ration of Al(2)O(3) and there temperature of annealing.